PENINGKATAN PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE PADA TEMA 6 SUBTEMA PENGARUH KALOR TERHADAP KEHIDUPAN SISWA KELAS V SEMESTER GENAP DI SDN TAROKAN 5 KECAMATAN TAROKAN KABUPATEN KEDIRI TAHUN PELAJARAN 2020/2021 - Titik Hariyani (KOLONI, 2022)
It is necessary to make learning innovations that can help improve students' understanding and reasoning to anticipate these problems. One of the efforts that can be taken is by applying a more effective learning model. Scramble learning model is one of the learning models that can be applied to improve students' creative thinking skills. Based on the background of the problem, the following problems can be formulated (1) How to apply the Scramble Type Cooperative Learning Model to improve student learning achievement In Theme 6 Sub-theme The Effect of Heat on the Life of Class V Students in Even Semesters at SDN Tarokan 5, Tarokan District, Kediri Regency, 2020 Academic Year /2021? (2) How to Improve Student Achievement Using the Scramble Type Cooperative Learning Model in Theme 6 Sub-theme The Effect of Heat on the Life of Even Semester V Graders at SDN Tarokan 5 Tarokan Sub-district, Kediri Regency, 2020/2021 Academic Year? In accordance with the type of research chosen, namely action research, this research uses the research model of Kemmis and Taggart, which is in the form of a spiral from one cycle to the next. Each cycle includes planning (plans), action (actions), observation (observations), and reflection (reflection). The steps in the next cycle are revised planning, action, observation and reflection. Before entering the first cycle, preliminary actions were carried out in the form of problem identification. From the results of the research conducted, it was found that in Cycle I, there were 4 students or 40% who achieved complete learning, Cycle II there were 6 students or 60%, who had achieved complete learning, and Cycle III there were 9 students or 90%, which have achieved mastery of learning. Based on the results of the research that has been done, the researchers can draw conclusions (1) The application of the Scramble Type Cooperative Learning Model can improve student learning achievement in Theme 6 Sub-theme The Effect of Heat on the Life of Even Semester V Class Students at SDN Tarokan 5, Tarokan District, Kediri Regency for the 2020 Academic Year/ 2021. (2) Improving Student Achievement Using the Scramble Type Cooperative Learning Model in Theme 6 Sub-theme Effect of Heat on the Life of Even Semester V Grade Students at SDN Tarokan 5 Tarokan District, Kediri Regency Academic Year 2020/2021 Cycle I (40%), Cycle II (60 %), and cycle III (90%). Keywords: Scramble type cooperative learning model, learning achievement